Characterization of marine bacterial isolate, Flammeovirga sp. UPMSI-L001 and assay of its carrageenolytic activity - Regalia, Raymond Sabio 1975- (2007)
A carrageenan-degrading marine bacterium, UPMSI-L001, previously isolated from ice-ice-infected thalli of Kappaphycus alvarezii was characterized. This bacterium which forms colonies with deep and wide depression on solidified culture medium is Gram-negative, rod-shaped, aerobic, chemoorganotropic and non-flagellated but apparently motile by gliding. It is capable of growth at 25ºC and 30ºC and at6 NaCl concentrations between 1-10%. Phylogenetic analysis of its 16S rDNA sequence revealed its close affiliation with the genus Flammeovirga. It is however distinct from its closest relative, Flammeovirga yaeyamensis by being non-pigmented and urease-positive and by having an oxidative type of glucoes utilization. The carrageenase production in liquid cultures. Several culture media were compared and the highest carrageenase activity (127.6 U/ml) was obtained in a seawater-based culture medium (SWM) supplemented with yeast extarct (5g/L) and trytone (5g/L). It was also found that this isolate had iota-carrageenase (59.7/ml) and lambda-carrageenase(54.7/ml) activities. This study is the first report on a Flammeovirga species that is associated with ice-ice disease in Kappaphycus alvarezii and has broad-range carrageenolytic activity. This strain has the potential to be used for the production of carrageenases for various biotechnological applications.